1999
DOI: 10.1039/a808745h
|View full text |Cite
|
Sign up to set email alerts
|

A flexible method of carbonate determination using an automatic gas analyzer equipped with an FTIR photoacoustic measurement chamber

Abstract: A Fourier transform infrared spectrometer was employed to determine automatically the total inorganic carbonate (TIC) in solids and waters, based on active photoacoustic absorption of infrared light by carbon dioxide. A 2.0 l reactor, connected to the spectrometer, is immersed in water-bath at 20 °C. After purging with pure N 2 , 5 ml of 0.5 mol l 21 HClO 4 are injected into 50 ml of solid suspension or solution with continuous stirring. The specific absorption of infrared light by the CO 2 evolved induces cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…So, for the instrumental calibration, the optimal resolution is 4 cm 21 because it solves the problem of non-linearity observed in previous FTIR-ATR determination of carbonate in soils, 4,6 covering almost the whole natural range of IC in environmental solid samples.…”
Section: Optimisation Of the Calibration Procedures For The Ftir-atr ...mentioning
confidence: 99%
See 2 more Smart Citations
“…So, for the instrumental calibration, the optimal resolution is 4 cm 21 because it solves the problem of non-linearity observed in previous FTIR-ATR determination of carbonate in soils, 4,6 covering almost the whole natural range of IC in environmental solid samples.…”
Section: Optimisation Of the Calibration Procedures For The Ftir-atr ...mentioning
confidence: 99%
“…3 The IC content of waters and solids has been measured by the photoacoustic absorption of IR radiation. 4 High resolution FTIR spectroscopy has been used to measure the 13 C + 12 C ratio in CO 2 evolved from soils and rocks. 5 These methods which require a preliminary acid or combustion step to convert carbonate into CO 2 , are very sensitive and reproducible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The band at 800 cm −1 corresponds to an inter-tetrahedral Si–O–Si bending vibration mode, and the band near 945 cm −1 to an Si–OH vibration mode [37]. Previous studies have shown that the absorbance centered around 1640 cm −1 and between 3000 and 3750 cm −1 can be attributed to hydroxyl vibrations because hydroxyl ions are major constituents of clay minerals, opal, and organic compounds present in marine sediments [38]. However, these bands are not specific for silica, their intensity is generally low (about one-tenth of the main band); moreover, they are overlapped with the residual absorption bands of H 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…In view of widespread occurrence of carbonate and bicarbonates in physiological, industrial and environmental samples, there exists a necessity of a durable, accurate and rapid sensor for biomedical applications, clinical and environmental analysis with potential for real sample investigation without interference from endogenous substrates [20][21][22][23][24][25][26]. A number of analytical methods have been developed for carbonate detection including Fourier transform infrared (FT-IR) spectroscopy [27], passive acoustic emission [28,29], gas chromatography [30], pH-ion-sensitive field-effect transistor as a sensitive element [31,32], ionselective electrodes [19,[33][34][35] and chromoionophore based optodes [36]. Alongside, the development of luminescent signalling systems utilising organic chromophores is an active area of research in photochemistry to establish fluorescent chemosensors which can be applicable to industry, diagnostic and various kinds of environmental monitoring.…”
Section: Introductionmentioning
confidence: 99%